Analisis Dampak Pengembangan Pulau Bokori Terhadap Perubahan Kesejahteraan Masyarakat Bajo di Desa Mekar Kecamatan Soropia Kabupaten Konawe - Darwan, Darwan; Yunus, Lukman; Fyka, Samsul Alam; Limi, Muhammad Aswar (Department of Agribusiness, Halu Oleo University, 2019)
The purpose of this study was to determine the impact of developing bokori islands on the welfare of the Bajo community. This research was conducted in Mekar Village. The research sample was 58 people. This research method is descriptive quantitative, namely to describe the level of welfare based on BPS measures, namely the level of income, income level, access to education, health, living conditions and facilities owned both before and after the development of Bokori Island. The data used are quantitative data that are statistically analyzed using T-Paired Sample Analysis. Results of discussion on community welfare when viewed through income, and doing medication, ownership of transportation equipment, electronic equipment, and home ownership tends to increase. So that it can be concluded that the welfare of the community after the development of Bokori tourism has increased. Although the ability to access education has not changed.